LC-MS/MS procedure for the simultaneous determination of N-acetyl-S-(1-naphthyl)cysteine and N-acetyl-S-(2-napthyl)cysteine in human urine - Zobel, Melanie; Klotz, Katrin; Göen, Thomas (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2018)
A two-dimensional liquid chromatographic electrospray-ionization tandem mass spectrometric (LC/LC-ESI-MS/MS) procedure for the simultaneous determination of the expected mercapturic acids of naphthalene (1- and 2-naphthylmercapturic acids; 1- and 2-NpMA) and of the well-established parameter for benzene biomonitoring (S-phenylmercapturic acid; PhMA) in human urine was developed, validated and applied to human urine samples. Apart from sample acidification, the enrichment of analytes and sample clean-up as well as the separation of all analytes were completely automated using both a restricted access material column (RAM C18) and a core-shell biphenyl material. Sensitive, specific and reliable detection of all target substances, with limits of detection ranging from 0.03 to 0.04 μg/L, was achieved using structurally well matching isotope-labelled internal standard substances for each analyte. Intraday and interday precision were determined, ranging from 2.2 to 4.3%, and mean accuracy from 98.4 to 100.8%. Due to the low limits of detection, the good precision and accuracy of the developed procedure, it is well suited for application in biomonitoring studies to evaluate the validity of mercapturic acids as biomarkers after naphthalene exposure.
EVALuna2:33781